2023
DOI: 10.1039/d2tc04416a
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of GNR-C60 single-molecule devices

Abstract: Based on the successful achievement of graphene-C60 single-molecule transistors in experiments, a series of double-layered GNR-C60, X/GNR-C60 (GNR=graphene nanoribbon; X=H, O, S, passivated edge atoms), devices are designed and their...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Encouragingly, both BIB 0 and ABIIA 0 B 0 devices possess large magnitudes of R (4400) under low biases (B1.0 V). In our previous work, 76 pronounced NDR behavior was also observed in Fe-free C 60 -GNR devices for different electrode linkages. However, the largest R value among Fe-free devices is 38.7, much smaller than 719 observed in the Fe-containing system ABIIA 0 B 0 .…”
Section: Transport Propertiesmentioning
confidence: 61%
See 1 more Smart Citation
“…Encouragingly, both BIB 0 and ABIIA 0 B 0 devices possess large magnitudes of R (4400) under low biases (B1.0 V). In our previous work, 76 pronounced NDR behavior was also observed in Fe-free C 60 -GNR devices for different electrode linkages. However, the largest R value among Fe-free devices is 38.7, much smaller than 719 observed in the Fe-containing system ABIIA 0 B 0 .…”
Section: Transport Propertiesmentioning
confidence: 61%
“…Most PIQ systems show double NDR peaks in the bias range of 0.0–1.4 V. In fact, double NDR character also exists in original C 60 -GNR devices with similar peak heights to PIIQ systems. 76 This means that high magnetism can be introduced from C 60 -GNRs to Fe 4 /C 60 -GNRs without influencing the transport properties significantly. At V = 0.4–0.8 V, the currents in PIIQ are negligible (<0.02 μA), suggesting that the transporting channel is in an off-state.…”
Section: Resultsmentioning
confidence: 99%
“…Such sequence of AB&A'B' > A&A' > B&B' > B&A' is inherited from the Fe-free C 60 -GNR devices. [80] A common reason is as bellow. Electron transporting in AB&A'B' device could be via multiple channels that contained in other three devices, and thereby it gives the highest NDR peak among all the connections.…”
Section: Ndr Transport Propertymentioning
confidence: 99%
“…By using density‐functional theory (DFT) calculations they found that this device has strong electron‐vibron coupling and weak vibron relaxation, and can exhibit redox‐dependent Franck‐Condon blocking and avalanche transport phenomena. Our previous work also predicted the NDR behavior of a serials of single molecular devices based on C 60 ‐GNR [80] . In spite of the abovementioned achievements, single molecules of M@C n ‐GNR, with metal trapped in C n , have yet not been reported in literature as far as we know.…”
Section: Introductionmentioning
confidence: 96%
“…18 Currently, the characteristics of these newly discovered 2D carbon materials mean they are considered promising candidates for a wide range of applications, such as nanoelectronics, nanomechanics and optical devices. In addition, there are many other new carbon materials that have been predicted theoretically 19 and synthesized experimentally, 20 demonstrating that their theoretical prediction has become a very important tool for the development of carbon materials. [21][22][23][24] Recently, 2D heterostructures have attracted tremendous research attention.…”
Section: Introductionmentioning
confidence: 99%